Development of interactive multimedia based on educational games of plant parts and their functions to improve student learning outcomes - None Nur Fadila; Karimatus Saidah; Dhian Dwi Nur Wendha (Jurnal Pijar Mipa, 2023)
Natural Science (IPA) is an activity to study nature systematically through actual activities and trains students to think critically and objectively to achieve learning objectives. Using learning media in the learning process can support success in the learning process. This study aims to determine interactive multimedia development's validity, practicality, and effectiveness based on the educational game "Plant World" material about plant parts and their functions. This research uses the R&D (Research and Development) method with the ADDIE model, which consists of 5 stages, namely 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Data collection techniques using expert validation questionnaires, teacher and student responses, and pre-test and post-test evaluations were then analyzed using qualitative and quantitative descriptive. The results showed that the development of interactive multimedia based on the educational game "Plant World" with the validation of media and material experts obtained an average percentage of 86% very valid criteria, teacher responses received a percentage of 89% very practical criteria, and student responses obtained a percentage of 90% very good criteria. The effectiveness was obtained from the average pre-test result of 57.7 and the post-test of 81.7. It was found that the post-test value was higher than the pre-test value, and the specified KKTP was 75. Strengthened by the Paired Sample-test results obtained 0.001 <0.05, there is a significant difference between pre-test and post-test evaluation.